The Effectiveness of E-LKPD Based on Education for Sustainable Development (ESD) to Improve Students’ Critical Thinking Skills - Badruttamam, Muhammad Imam; Saptono, Sigit; Ellianawati, Ellianawati (Journal of Innovative Science Education, 2025)
Critical thinking is a crucial 21st-century skill that must be fostered through contextual and sustainable learning approaches. However, in the Indonesian curriculum, there is still a lack of digital learning tools explicitly designed based on Education for Sustainable Development (ESD), which limits opportunities to cultivate students’ critical thinking in environmental contexts. This study aims to examine the effectiveness of ESD-based electronic student worksheets (E-LKPD) in enhancing students’ critical thinking skills. The research employed a quasi-experimental design involving 138 senior high school students, divided into an experimental group (ESD-based E-LKPD) and a control group (conventional LKPD). The instrument used was a critical thinking test based on Facione’s five indicators: interpretation, analysis, evaluation, inference, and explanation. The results showed that the experimental group achieved a significantly higher normalized gain (N-Gain = 0.63, moderate category) compared to the control group (N-Gain = 0.30, low category), with a statistically significant difference (p < 0.05). Furthermore, 50% of students in the experimental group reached the high N-Gain category, while only 7% did so in the control group. These findings indicate that ESD-based E-LKPD is effective in improving students’ critical thinking skills and could serve as an innovative digital learning tool in environmental education.